Influencia del enfoque ecléctico en las habilidades productivas (habla y escritura) del idioma inglés en estudiantes de la educación media de la Unidad Educativa Católica La Victoria - Mera Giraldo, Rosa Silvana (2023)
Eclectic methodologies seem to be the most suitable way to learn a foreign language due to weaknesses in all known English teaching methodologies that do not involve all the skills but only focus on specific ones. Eclectic methodologies aim to avoid those weaknesses and use their pros according to students' necessities. If this type of approach is applied in the correct way, it could have really good results in L2 learning. Otherwise, students will continue with the same or different difficulties to learn the new language. In the case of the U.E.C. La Victoria, there is no specific methodology to apply, but the educator is free to choose strategies and techniques according to his/her convenience. This research paper is supported by classic scholars such as Jean Piaget in the learning process and Stephen Krashen in language acquisition issues. Furthermore, recent investigations related to eclectic methodologies and productive skills have been considered to enrich results with a scientific foundation and present an updated overview of the topic. The relevance of this research not only involves the mentioned institution but also English language education in our country, considering that productive skills acquisition and the management of the second language in general, is not so good, according to the statistics, even if the English subject is mandatory thought in all the country. In that way, the understanding and application of a project that could enhance productive skills acquisition is necessary.